(untitled) (Global Journal of Management and Business Research, 2014)
This paper discusses the importance and need of incorporating technology and innovation strategy into business strategy to achieve overall competitive advantage for the company. The use of technology and innovation in value creation system is highlighted in a way that it plays a pivotal role in productivity, economic growth, increasing wealth in socioeconomic environment, and evolution of entire industries. Strategy formation and execution in the context of technology is discussed that technology strategy should be aligned to corporate strategy in order to reap out benefits like performance and competitiveness for the company. Furthermore, concepts like technology strategy, forces affecting technology strategy formation and execution, technology management, innovation management, and what benefits companies can get from these are highlighted and discussed in relation to corporate business strategy.